Antiyeasts Activities of Garad (Acacia nilotica L.) and Rumman (Punica granatum L.) Plants - Eltayeb, Thowiba M.; . Abdel-Rahim, Awad M (Gezira Journal of Engineering and Applied Sciences; Vol 12 No 2 (2017), 2018)
Medicinal plants are sources of antimicrobial compounds. Some parts of these plants were reported to contain flavanoids, tannins, saponine, sterole and alkaloid. Compounds.. Garad and Rumman were reported to have some antimicrobial activities. The aim of this study is to investigate and analyze the phytochemical compounds and the antiyeasts activities of these two plants. The cup plate Inhibition zone method was used for the solvents tested. The inhibition zone tests showed that the Garad leaves and pods extracts were highly effective against C. albicans , and bark extract was highly effective against C. valida . The bark and the seeds extracts were effective against C. tropicalis, while, the pods extract was more effective against Pichia sp. Rumman peels extracts were more effective against       C. tropicalis . The solvent tests showed that the methanolic pod extracts of Garad were effective against Pichia sp. and C. tropicalis . The leaves extracts were effective against C. albicans . while, the bark extracts were effective against C. tropicalis and C. valida .  However, the seeds extracts were effective against C. albicans, C. valida , and C. tropicalis . The methanolic Rumman peels extracts were effective against C. valida.          C. valida was the only sensitive yeast against the bark and the peel ethanolic extracts of Rumman. All the petroleum ether and hexane extracts of the two plants parts were not effective against all the tested yeasts. Both Garad and Rumman plants were containing inhibitory compounds against different yeasts. The study suggestes that further stidies on the extracts of both Garad and Rumman should be made before being  for treating